Do Policy Maker Creates Financial Innovation And Support Growth? - Suwinto Johan (Universitas Tarumanagara, 2019)
The financing industry has grown rapidly for more than 40 years of enactment of the 3 ministerial regulations in 1974. The regulations that governing this industry have also been updated several times by the related authorities from time to time, directly under the supervision of the Minister of Finance to Capital Market Supervisory Agency and Financial Institution of Indonesia (Bapepam LK) until now by the Financial Services Authority (OJK). The type of businesses that can be run also has grown from the lease type of financing to capital financing, multipurpose financing and investment financing at this time. This study examines the development of financing industry in line with the regulatory changes. The study conducted a qualitative study as literature and secondary. This study found that the growth of financing industry can be divided into 3 period in accordance with the regulations that have been issued. These three periods are 1974-1988, 1988-2015 and 2015-2017 (current). Also, this study found that changing regulation has supported the development of the financing industry from time to time. The further study is needed to examine the development of financing industry since the issuance of PJOK in 2015